1994
DOI: 10.1080/09553009414551251
|View full text |Cite
|
Sign up to set email alerts
|

Dose and Dose-rate Dependence of the Frequency of HPRT Deficient T Lymphocytes in the Spleen of the137Cs γ-irradiated Mouse

Abstract: The frequency of hypoxanthine phosphoribosyl transferase (HPRT) deficient splenic T lymphocytes was measured in the 137Cs gamma-irradiated mouse by the T cell cloning method. Doses from 0.3 to 6 Gy were applied at the dose-rates 0.5 Gy/min, 1 Gy/day and 1 Gy/week. Mutants were determined 8-10 and 30-40 weeks after the end of exposure. Radiation-induced mutant frequency (MFi) was calculated by subtracting the age corrected spontaneous mutant frequency (MFsp) from total mutant frequency (MF) found in irradiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…1A), fractionation at daily intervals seemed to be more efficient for this mutational induction than fractionation at weekly intervals (median, 67 Â 10 À6 versus 31 Â 10 À6 ; P < 0.03). This finding is consistent with the report that, given the same dose, acute exposure was more effective in inducing Hprt mutations in mouse T cells (20) although the underlying mechanisms remain unknown. In contrast to the remarkable increase in the IR-induced mutant frequency at the Hprt locus, there was only a modest increase in the IR-induced mutant frequency as a function of dose at the Aprt locus.…”
Section: Resultssupporting
confidence: 83%
“…1A), fractionation at daily intervals seemed to be more efficient for this mutational induction than fractionation at weekly intervals (median, 67 Â 10 À6 versus 31 Â 10 À6 ; P < 0.03). This finding is consistent with the report that, given the same dose, acute exposure was more effective in inducing Hprt mutations in mouse T cells (20) although the underlying mechanisms remain unknown. In contrast to the remarkable increase in the IR-induced mutant frequency at the Hprt locus, there was only a modest increase in the IR-induced mutant frequency as a function of dose at the Aprt locus.…”
Section: Resultssupporting
confidence: 83%
“…Comparison of these results with ours suggests that there may be a threshold dose at which sparing of mutant frequency induction occurs in a daily exposure plan (50 cGy being below, 1 Gy dose being above). Consistent with the existence of a threshold for sparing in mutation induction, 8-10 weeks after chronic exposures to g radiation (dose rates of 1 Gy/day and 1 Gy/week) Lorenz et al [1994] observed lower efficiency of induction of Hprt deficient mutants than after acute dosing (50 cGy/min). On a practical level, dose fractionation can induce sufficiently elevated mutant frequencies that molecular mutation spectra associated with small acute doses might be compared to spectra of background and high doses.…”
Section: Discussionsupporting
confidence: 56%
“…The occurrence of dosedependent radiation mutagenesis in mice has been demonstrated in a number of studies [Dempsey and Morley 1986;Lorenz et al, 1990Lorenz et al, , 1993Lorenz et al, , 1994Grdina et al, 1992;Kataoka et al, 1992Kataoka et al, , 1993Gaziev et al, 1995;Klarmann et al, 1995;Dobrovolsky et al, 2002;Liang et al, 2007]. However, the more extensive evaluation of time elapsed after acute g irradiation revealed that mutant frequency dependence on dose shifted between 3 and 5 weeks and 10-53 weeks, from being clearly quadratic at the peak of mutant recovery in weeks 3-5 to a statistically strong but less-defined dose relationship in the later time frame.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are very few studies of DREs on HPRT mutations in vivo in the very low DR range (21), so it is difficult to decide whether there is an inverse DRE. However, mutant frequencies were elevated in lymphocytes of humans exposed to low doses of ionizing radiation at low and͞or very low DRs (22)(23)(24)(25), relative to high DRs.…”
Section: Evidence For Inverse Dresmentioning
confidence: 99%